2008
DOI: 10.1111/j.1542-474x.2008.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Heart Rate Variability and Plasma N‐Terminal Pro‐B‐Type Natriuretic Peptide in Healthy Subjects: Is There the Relationship between Both Markers?

Abstract: These findings could contribute to the higher rate of cardiovascular events in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
30
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
8
30
1
3
Order By: Relevance
“…4,11 In the present study, lower cardiac vagal modulation supported by lower values of time domain measures agrees various other investigators. 11,12,13,14 Also, the significantly lower mean R-R interval in all smokers compared to non smokers were comparable to the findings of Barutcu et al 15 The reduced cardiac vagal modulaion and the simultaneous sympathetic hyperactivity in the smokers of this study may be the effect of consumption of nicotine and other substances contained in cigarette smoke and this view is shared by several groups of researchers. 4,11,12,[15][16][17] In smokers, the higher value of mean heart rate indicates higher sympathetic and lower values of mean R-R interval, SDNN and RMSSD indicates lower parasympathetic activity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…4,11 In the present study, lower cardiac vagal modulation supported by lower values of time domain measures agrees various other investigators. 11,12,13,14 Also, the significantly lower mean R-R interval in all smokers compared to non smokers were comparable to the findings of Barutcu et al 15 The reduced cardiac vagal modulaion and the simultaneous sympathetic hyperactivity in the smokers of this study may be the effect of consumption of nicotine and other substances contained in cigarette smoke and this view is shared by several groups of researchers. 4,11,12,[15][16][17] In smokers, the higher value of mean heart rate indicates higher sympathetic and lower values of mean R-R interval, SDNN and RMSSD indicates lower parasympathetic activity.…”
Section: Discussionsupporting
confidence: 76%
“…As a major component of cigarette smoke, nicotine stimulates the nicotinic receptors of autonomic ganglia as well as adrenal medulla resulting in increased cardiac sympathetic activity and increased release of catecholamine. 12,[18][19] This effect is obviously attributed to the higher heart rate and the restriction of heart rate variability in the smokers of this study. This effect of nicotine may be further intensified by its action on peripheral chemoreceptors causing impaired baroreflex sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Alyan et al 28 avaliaram os efeitos do tabaco na VFC entre adultos jovens (cerca de 35 anos), fumantes e não fumantes de ambos os sexos, e observaram uma redução nos índices rMSSD e AF.…”
Section: Discussionunclassified
“…Further, smoking cessation ameliorates these conditions. The studied by Omer et al 7 with 75 healthy habitual smokers (40 females, 35 males, mean age 36.5 ± 8.5 years), and 73 nonsmokers (45 females, 28 males, mean age 34.6 ± 7.2 years). Additionally, found that smoking resulted in an increase NT-pro-BNP levels and there was a significant positive correlation observed between the duration of smoking and NT-pro-BNP levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have reported usefulness of measurement of plasma BNP levels as a biomarker for the detection and follow-up of heart diseases and a risk factor for death independent of COPD. 6,7 Studies related to BNP levels in Stable COPD patients without PH or COR-P however, are limited. 2,8,9 The aim of the present study was to investigate the use of plasma BNP levels as a prognostic marker in patients with stable COPD during exacerbation and after remission.…”
mentioning
confidence: 99%